EDEM1 Inhibits Endoplasmic Reticulum Stress to Induce Doxorubicin Resistance through Accelerating ERAD and Activating Keap1/Nrf2 Antioxidant Pathway in Triple-Negative Breast Cancer - Yajie Wang; Yiran Liang; Dan Luo; Fangzhou Ye; Yuhan Jin; Lei Wang; Yaming Li; Dianwen Han; Zekun Wang; Bing Chen; Wenjing Zhao; Lijuan Wang; et al. (Research)
Doxorubicin (DOX)-based chemotherapy is the basic treatment for triple-negative breast cancer (TNBC). However, chemoresistance is still one of the major causes of metastasis, recurrence, and poor outcomes. Recently, a close relationship between chemoresistance and endoplasmic reticulum (ER) stress has been found. In this study, ER-associated degradation (ERAD)-related protein EDEM1 (ER degradation enhancing α-mannosidase-like 1) plays a vital role in DOX-induced ER stress, which is up-regulated in tumor cells and tissues. In vitro and in vivo experiments reveal the promoting role of EDEM1 in the progression and chemoresistance of TNBC. Besides, EDEM1 attenuates autophagy and reduces ER stress-related apoptosis, indicating its inhibitory effect on ER stress. Furthermore, EDEM1 promotes ERAD and enhances the antioxidant capacity of tumor cells. Mechanistically, EDEM1 competitively binds Kelch-like ECH-associated protein 1 to prevent the ubiquitination and degradation of nuclear factor erythroid 2-related factor 2 (Nrf2), leading to increased Nrf2 nuclear translocation and antioxidant response element activation to bolster antioxidant defense and cell survival. Moreover, both the expression and function of EDEM1 are down-regulated by miR-32-5p. Clinically, high EDEM1 expression is correlated with poor patient outcomes in breast cancer, especially in TNBC patients treated with DOX-based chemotherapy. These findings reveal EDEM1 as a regulator of ER homeostasis during cancer progression and chemoresistance, and a potential target for breast cancer therapy.